1866 Md. Laws 602, ch. 375 - (:unkn) unknown (General Publisher, 1866)
Prohibited the concealed carry of any pistol, dirk-knife, Bowie-knife, slung-shot, billy, sand-club, metal knuckles, razor, any other dangerous or deadly weapon. Violators fined not more than five hundred dollars, or imprisoned not more than six months.
--
Keywords: CARRY - CONCEALED